Navigating challenging settings: bureaucrats’ policy entrepreneurship and divergence practices within Brazil’s environmental and indigenous agencies - Silveira, Mariana Costa (2024)
Bureaucrats play a crucial role in public administration as they can influence policy processes and potentially change policy design and outcomes. This dissertation consists of three articles that examine the organizational and individual factors that influence bureaucrats’ behavior in their efforts to shape policy-making. We explore two concepts: policy entrepreneurship (PE) and dissent attitudes among bureaucrats. We refer to policy entrepreneurship as the mission-oriented attempts of bureaucrats to influence policy-design and bring about policy change. We refer to dissent behavior as the mission-oriented practices of bureaucrats that oppose the wishes of their superiors. Although both forms of behavior - PE and dissent - may significantly alter the course of policies, the existing literature on public administration has overlooked the organizational and individual factors influencing them. To address this gap, we sought to answer the following research question: how do organizational and individual factors influence bureaucrats’ policy entrepreneurship and dissent attitudes? To answer this question, we conducted a pre-registered survey experiment and 82 in-depth semi-structured interviews with bureaucrats working in the environmental and indigenous sector of the Brazilian federal government. In the first article, we examine the organizational factors that influence bureaucrats’ dissent attitudes in a context marked by abusive supervision and politician-bureaucrat misalignment. Our findings indicate that when bureaucrats have the support of their colleagues and professional associations, they are more likely to engage in dissent. The second article provides insights into how professional associations (PAs) can assist bureaucrats in navigating dissent and assesses the impact of PAs on bureaucratic dissent attitudes. The results indicate that bureaucrats with different individual characteristics will engage in different dissent practices, even when presented with the same organizational source of support (i.e., support from PAs). The third article investigates how bureaucrats adapt their PE practices based on their perceptions of changing political and organizational contexts. We find that bureaucrats strategically adjust their PE practices in response to perceived constraints and opportunities within their organizational and political settings. The findings from these three articles contribute new insights to the existing literature on policy entrepreneurship, divergence, and behavioral public administration. We provide novel evidence and theoretical insights, particularly regarding the organizational and individual-level factors influencing bureaucrats' attitudes and practices towards PE and divergence within public administration.